The importance of microalbuminuria screening in persons with hypertension and with or without diabetes - Severović, Saška; Bojić, Gordana; Đorđević, Dragan (General Practice, 2025)
Introduction. Albumin is a protein produced in theliver, playing a crucial role in maintaining osmotic pressureand transporting molecules. Microalbuminuria, which is thepresence of small amounts of albumin in urine, often depictsthe damage to kidney function as well as the risk of developingcardiovascular and cerebrovascular diseases.Objective. We aimed to establish the prevalence of microalbuminuriain patients with hypertension and diabetes,and to estimate the prevalence in the difference between thesegroups and the control group.Method. The study encompassed 139 patients, separatedinto the exposed group (patients with hypertension anddiabetes) and the control group. Microalbuminuria testingwas performed using qualitative test strips. These strips detectalbumin in urine. For statistical analysis, we used Chisquare- χ2 test to evaluate the difference between the groups.Results. The prevalence of microalbuminuria in the exposedgroup was 33,09%. Statistically significant differencein the prevalence of microalbuminuria between the exposedand the control group was confirmed with p-values below0,05. There were no significant differences in distribution accordingto gender and age.Conclusion. Microalbuminuria was registered in significantpercentages in patients with hypertension and diabetes,which necessitates the need for regular screening in orderto timely detect changes in kidney function and calculate therisk of cardiovascular diseases.
Keywords: proteinuria; kidney diseases; risk assessment; biomarkers; early diagnosis